Development of motor innervation of the chick following dorsal-ventral limb bud rotations - Ferguson, BA (J Neurosci, 1983)
To test mechanisms which motoneurons may use to grow to their appropriate targets, I rotated the limb around the dorsal-ventral axis prior to motoneuron outgrowth. The positions of motoneurons in the spinal cord innervating individual muscles and muscle masses were then determined using retrograde horseradish peroxidase uptake. Motoneurons innervated their appropriate muscles after dorsal-ventral limb rotation, before and after motoneuron death. Thus, cell death does not serve to remove errors in matching between motor nuclei and their corresponding muscles after dorsoventral rotation of the limb. Motoneurons must be specified for a peripheral target prior to outgrowth, and they grow to that target relatively directly. Axons compensated for the limb rotation by first collecting into groups in a position appropriate for the normal limb orientation, then shifting dorsal-ventral position within the plexus and proximal nerve trunk. Based on these results it is hypothesized that axons destined to innervate dorsal or ventral musculature might use chemospecific cues during growth to maintain appropriate positions within the nerve with respect to limb orientation.